Comparison of interventional and surgical myocardial revascularization in kidney transplant recipients – A single-centre retrospective analysis. (December 2018) - Lang, Jeannine; Buettner, Stefan; Weiler, Helge; Papadopoulos, Nestoras; Geiger, Helmut; Hauser, Ingeborg; Vasa-Nicotera, Mariuca; Zeiher, Andreas; Fichtlscherer, Stephan; Honold, Joerg
Abstract: Background: Kidney transplant recipients (KTR) reflect a high-risk population for coronary artery disease (CAD). CAD is the most common cause for morbidity and mortality in this population. However, only few data are available on the favourable revascularization strategy for these patients as they were often excluded from studies and not mentioned in guidelines. Methods: This retrospective single-centre study includes patients with a history of kidney transplantation undergoing myocardial revascularization for multivessel or left main CAD by either percutaneous coronary intervention (PCI, n = 27 patients) or coronary artery bypass grafting (CABG, n = 24 patients) at University Hospital Frankfurt, Germany, between 2005 and 2015. Results: In-hospital mortality was higher in the CABG group (20.8% vs. 14.8% PCI group; p = 0.45). In Kaplan-Meier analysis, one-year-survival showed better outcome in the PCI group (85.2% vs. 75%). After four years, outcome was comparable between both strategies (PCI 66.5% vs. CABG 70.8%; log-rank p = 0.94). Acute kidney injury (AKI), classified by Acute Kidney Injury Network, was observed more frequently after CABG (58.3% vs. 18.5%; p < 0.01). After one year, graft survival was 95.7% in the PCI group and 94.1% in the CABG group. Four year follow-up showed comparable graft survival in both groups (76.8% PCI and 77.0% CABG; p = 0.78). Conclusion: In this retrospective single-centre study of KTR requiring myocardial revascularization, PCI seems to be superior to CABG with regard to in-hospital mortality, acute kidney injury and one-year-survival. To optimise treatment of these high-risk patients, larger-scaled studies are urgently warranted.